New and little-known digger wasps (Hymenoptera: Ampulicidae, Sphecidae, Crabronidae) from Russia - Mokrousov, Mikhail V.; Proshchalykin, Maxim Yu. (Zootaxa, 2021)
New additions to the knowledge of digger wasps (Ampulicidae, Sphecidae, Crabronidae) in Russia are provided. Tachysphex loktionovi Mokrousov & Proshchalykin, sp. nov. is described from Tyva Republic. Five species of digger wasps are reported from Russia for the first time: Hoplammophila clypeata (Mocsáry, 1883) (Sphecidae), Tachysphex desertorum F. Morawitz, 1894, T. mongolicus Kohl, 1898, Tachytes argenteus Gussakovskij, 1933, and Trypoxylon albipes F. Smith, 1856 (Crabronidae). Misidentified Tachysphex speciosissimus Morice, 1897 (=T. gussakovskii Pulawski, 1971) is excluded from the fauna of Russia. Hitherto unknown male of Tachysphex mongolicus Kohl, 1898, stat. resurr. is described and regarded as a valid taxon. New synonymy is proposed for T. mongolicus Kohl, 1898 = T. abditus Kohl, 1898, syn. nov. Diagnosis for male of Dolichurus haemorrhous A. Costa, 1886 is updated. New regional records for seven species are recorded. The known fauna of Russia currently numbers three families, 87 genera and 694 species of digger wasps. In addition Tachytes argenteus Gussakovskij, 1933 is reported for the first time from Uzbekistan and Cyprus, and Trypoxylon beaumonti Antropov, 1991 is newly recorded from Ukraine.